Congolese Medicinal Plant biodiversity as Source of AntiCOVID-19 Compounds: Economic goods in the light of Comparative Advantages Theory of Ricardo - Modeste Ndaba Modeawi; Ruphin Djolu Djoza; Colette Masengo Ashande; Clarisse Falanga Mawi; Emmanuel Moke Lengbiye; Clément Inkoto Liyongo; Benjamin Gbolo Zoawe; Muhammad Ridwan; Pius T. Mpiana; Mudogo Virima; Koto-te-Nyiwa Ngbolua (Budapest International Research and Critics University, 2020)
Since the outbreak of Covid-19 (Corona virus) in China in December 2019, the disease has killed more people in Europa, America and Asia according to official sources. Less impacted than the rest of the world, Africa as well as Oceania has less confirmed cases and less deaths. In countries whose health systems are among the most fragile in the world, with far less resources than those mobilized in Europe, China or the United States, the situation in Africa is potentially catastrophic. Since human and material resources, such as hospitalization and intensive care beds, are largely insufficient, the mortality rate linked to Covid-19 is likely to be 3 to 5 times higher than in the rest of the world. In the face of this evidence, scientific research based on medicinal plants would be seen as no less important part of the solution to the Covid-19 pandemic, based on plant biodiversity. The Malagasy Institute of Applied Research (IMRA/Madagascar) on the basis of the Artemisia annua has set up Covid-Organics; The Congolese plant biodiversity offers undeniable advantages for the setting up of an Improved Traditional Medicine following the example of Covid-Organics. This would constitute for the Democratic Republic of the Congo a comparative advantage to be put forward in its multiple international exchanges.